Jesse Jackson for President Rally at Warnor's Theatre - Watkins, Howard::::::::: (1984)
??, Wally Porter, Jesse Jackson shaking hands with Chris Petersen, ?, Lorri Foster, ?, Arturo Vasques, and Aubrey Stone